IDENTIFIKASI DAN STRATEGI PENURUNAN PENGANGGURAN DI KOTA PEKALONGAN - Madusari, Beny Diah; Imtihanah, Sobrotul; Pratikwo, Suryo; Ismanto, Kuat (BAPPEDA Kota Pekalongan, 2020)
This study aimed to map and formulate a policy about unemployment in Pekalongan City, focusing on three things; the reasons of unemployment cause, people’s interest of desired work, and an unemployment reducing policy. As a research method, we carried out a qualitative descriptive and used an open questions-questionnaire as the media for a hundred respondents, spread in 4 districts; Pekalongan Utara, Selatan, Barat, and Timur (Northern, Southern, Western, and Eastern Pekalongan). And in completing the study result, we also held a Focus Group Discussion (FGD) by inviting the budgeting-interested stakeholders. The results indicated three points; (1) a type of unemployment in Pekalongan is a frictional one; a condition where the jobless workers want to earn better wages, (2) a big interest of people to be an entrepreneur based on the big income and more time. And also, they hope the local government will support them in term of their capital easily and cheaply, and (3) from FGD, it resulted a suggestion to initiate ‘a creative house’ a media to accommodate the workshops outputs, and to formulate a regulation which obligate every business in Pekalongan to involve the local workers. Keywords: Pekalongan, unemployment reduce, unemployment causes